Psychological well-being and burden in caregivers of patients with schizophrenia - Aditya Gupta; RK Solanki; GD Koolwal; Sanjay Gehlot (Universiti Kebangsaan Malaysia, 2015)
Background: There is a definite paucity of Indian studies looking into the caregiver burden, psychological well-being, and the interface between them. Objectives: This work aims to study the correlation between these variables. Materials and Methods: The study sample included 100 patients with a diagnosis of schizophrenia and their caregivers, randomly selected from the patients admitted in the male and female wards of psychiatric center, Jodhpur, as per inclusion and exclusion criteria. Burden Assessment Schedule and Psychological General Well-Being Index were used for the study. Results: Eighty percent of the caregivers experienced moderate levels of burden. The burden was higher among older (r = 0.334) caregivers and spouse (p o 0.0001). Psychological well-being was low in older caregivers (r = -0.44) and those with lower educational status, and higher in the siblings (p = 0.002). A strong negative correlation was found between burden and psychological well-being (r = -0.81). Conclusion: Quality of care given to the individuals with schizophrenia depends on their primary caregiver. It thus becomes essential to plan interventions that would reduce their burden of care and thus improve their psychological well-being.